2018
DOI: 10.1007/s10815-018-1223-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blastocoel cell-free DNA and day-5 blastocyst morphology

Abstract: This study provides further evidence that cfDNA is present in blastocoel fluid, can be quantified, and positively correlates with embryonic morphology. There is also evidence that at least a portion of the cfDNA present is from intracellular contents of embryonic cells that underwent apoptosis. Additional studies are warranted to determine other physiological sources of the cfDNA in blastocyst fluid and to determine the relationship with cfDNA content, embryo morphology, and chromosomal ploidy status plus impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Previous studies have reported that the concentration of cfeDNA correlates with apoptotic events 44 . We hypothesized that lower grade blastocysts, which tend to have a higher rate of apoptosis, will release a higher quantity of cfeDNA into the medium.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have reported that the concentration of cfeDNA correlates with apoptotic events 44 . We hypothesized that lower grade blastocysts, which tend to have a higher rate of apoptosis, will release a higher quantity of cfeDNA into the medium.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism(s) underlying the release of embryonic DNA into the culture medium remain unclear and the origin of these DNA fragments is unknown 2,7,43 . The most popular hypothesis is that nucleosome sized DNA fragments (~180-200 bp) are being released from cells as a result of apoptosis 27,38,40,44 . Another mechanism that could contribute cell free DNA with longer sized DNA fragments is necrosis 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the application of cfDNA analysis from spent media as a replacement for PGT-A is problematic and risky at best, there may yet be means through which cfDNA can provide critical information about a preimplantation embryo alongside PGT-A. In our lab's research, we have observed that the quantitative analysis of cfDNA content have been directly correlated to both preimplantation embryo morphology and ploidy status (Rule et al, 2018;Chosed et al, 2019). Since it has been reported that the quantity of cfDNA is correlated with ploidy status, one way to utilize the blastocoel fluid would involve measuring cfDNA quantity as a confirmational check to any PGT-A result, potentially providing a second determinant of embryo quality (Chosed et al, 2019).…”
Section: Potential Applications Of Blastocoel Componentsmentioning
confidence: 82%
“…Recent literature points to an increased interest in using the information provided by blastocoel cfDNA alongside PGT-A as a cumulative measure of preimplantation embryo quality (Rule et al, 2018). Several reports have postulated that competent preimplantation embryos may be identified via cfDNA content in the blastocoel fluid or spent media (Assou et al, 2014;Werner et al, 2014).…”
Section: Blastocoel Fluid Componentsmentioning
confidence: 99%